Remarks on Gallagher's Enactivist Philosophy of Nature. Issue 2 (3rd April 2018) - Macarthur, David
Abstract: Shaun Gallagher's [2019] 'Rethinking Nature' is an attempt to make conceptual space for the relevance of the phenomenological tradition of Husserl, Merleau-Ponty, etc., to cognitive scientific explanation within an embodied enactivist approach to cognition. Since cognitive science currently presupposes orthodox scientific naturalism—for which nature is nothing over and above the objective posits of successful (typically natural) science—it makes no allowance for the lived first-person experiences or intersubjective agency that are central to phenomenology; and so, renders them unavailable to Gallagher's enactivism. Gallagher leading idea is to qualify the scientific naturalist idea of nature as a totality of 'objective' (i.e., mind-independent) physical objects in order to make allowance for subjects and their subjectivity in the scientific image of the world. In this proposal Gallagher continues to think within the scientific naturalist commitment to the completeness of the scientific image of the world. In this brief commentary, although I applaud Gallagher's description of the problem of subjectivity in relation to science, and his general strategy of rethinking nature, I criticize the specific form this rethinking takes. I argue that a better way to include irreducible subjects and subjectivity in a reconception of nature is to drop the requirement that everything in nature must figure in the scientific image of the world. Thus, I propose the advantages of a liberal naturalism (as I call it), and a retention of an objectivist conception of science, over Gallagher's reformed scientific naturalism.